Global corporate governance - John, Kose; Makhija, Anil K.; Ferris, Stephen P. (Emerald Publishing Limited, 2017)
Advances in Financial Economics Volume 19 deals with International Corporate Governance, particularly the role played by boards of directors, internal organization design and governance mechanisms, franchise agreements, the effect of regulation and policy, the market for corporate control, and strategic alliances.- Resumé vydavatel
Keywords: řízení a správa společností -- mezinárodní kontext; corporate governance -- international context; kolektivní monografie; elektronické knihy; collective monographs; electronic books